An on-line statistical process control application for wire bond - Liu, Hann Wen. (2008)
Implementing Computer Integrated Manufacturing (CIM) systems in semiconductor manufacturing can lead to better quality, increase production output and flexibility, through better utilization of automation, communications and other management systems. As Computer Integrated Manufacturing (CIM) Systems become more prevalent, emphasis is being placed upon effective quality control methods to ensure the system's operational success. Statistical Process Control (SPC) is a powerful collection of problem-solving tools useful in achieving process stability and improving capability through the reduction of variability. The importance of the SPC is being known by the industry for decades. Control charts are the basic tools to monitor the statistical process stability. This study is to introduce the implementation of on-line SPC process through computerization. On-line Process Control Automation System (PCAS) is an extension of the conventional Statistical Process Control (SPC) tool for achieving this objective. Process Control Automation System is the powerful on-line statistical process controls tools to automate the preparation of control charts and reports for the various SPC tests conducted, the data is stored in a Informix database. On-line statistical control graphs will be generated. The data will be transferred to the SAS/QC Statistical System, for plotting historical graphs and reports.